2009
DOI: 10.1002/ijc.24460
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors according to estrogen receptor status of breast cancer patients in Trivandrum, South India

Abstract: Estrogen receptor (ER) status is an important biomarker in defining subtypes of breast cancer differing in antihormonal therapy response, risk factors and prognosis. However, little is known about association of ER status with various risk factors in the developing world. Our case-control study done in Kerala, India looked at the associations of ER status and risk factors of breast cancer. From 2002 to 2005, 1,208 cases and controls were selected at the Regional Cancer Center (RCC), Trivandrum, Kerala, India. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 52 publications
5
79
1
Order By: Relevance
“…At 62 %, ER positivity is low when compared to the West, but similar to the other studies from India [3,[12][13][14]. That the proportion ER-PR-was found to be higher, supports the hypothesis that breast cancer tends to be more aggressive in young individuals [15].…”
Section: Discussionsupporting
confidence: 84%
“…At 62 %, ER positivity is low when compared to the West, but similar to the other studies from India [3,[12][13][14]. That the proportion ER-PR-was found to be higher, supports the hypothesis that breast cancer tends to be more aggressive in young individuals [15].…”
Section: Discussionsupporting
confidence: 84%
“…After careful and thorough reading, 4 articles have been again excluded for the following reasons Full text article not available (1), Not from South India (1), Study on Families of BC patients (1), and educational intervention on screening (1). Finally 16 articles have been selected for the qualitative synthesis (Gajalakshmi and Shanta, 1991;Nandakumar et al, 1998;Yeole and Kurkure, 2003;Kuraparthy et al, 2007;Ali et al, 2008;Mathew et al, 2008;Syamala et al, 2008a;2008b;Dey et al, 2009;Jayalekshmi et al, 2009;Syamala et al, 2009;Vaidyanathan et al, 2009;Harrison et al, 2010;Surekha et al, 2010;Chauhan et al, 2011) Methodological qualities of included studies: Out of 16 included studies 10 were Case studies, 1 Nested case control study (on a cohort of women), 4 studies were based on Secondary data analysis and 1 (Marmot et al, 2007) was cross-sectional study. Confounding factors were reported and adjusted in 2 out of 10 case control studies, mentioned and not controlled in 3 studies and not mentioned in rest of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Previous Indian studies have documented that rates of ER negativity is high among breast cancers in Indian women [2][3][4]. It has been suggested that factors contributing to this high ER negativity could be technical failures of detection of ER, younger age of patients, and advanced stage at presentation -all of which can increase the proportion of ER negative tumours [2].…”
Section: Discussionmentioning
confidence: 99%
“…lacking ER, progesterone receptor (PR) as well as HER-2 receptors [1]. Previous data from India show higher proportion of ER negative breast cancer compared to the west [2][3][4]. This higher burden of ER negative disease has been attributed to several factors, including technical failures at detection of ER positivity, younger age of patients, and advanced stage at presentation -all of which can increase the proportion of ER negative tumours [2].…”
Section: Introductionmentioning
confidence: 99%